Demographic characteristics of children with growth hormone deficiency from 1996 to 2015 in Japan: 20 years of data from the foundation for growth science in Japan - Tanaka, Toshiaki; Yokoya, Susumu; Hasegawa, Tomonobu; Isojima, Tsuyoshi (Endocrine Journal, 2022)
Growth hormone (GH) deficiency (GHD) in children is a heterogeneous condition that includes several entities of various severities. GH treatment has been affected by various factors. Because comprehensive analyses for Japanese children with GHD over time are scarce, we investigated the baseline characteristics of patients with GHD at the start of GH treatment between 1996 and 2015 using data from the Foundation for Growth Science in Japan. During the registration period, 19,717 subjects were determined to be eligible for GH treatment as GHD. Overall analyses revealed that there were twice the number of male patients as female patients, and the etiology was idiopathic in 91.1%, central nervous system (CNS) tumor at the hypothalamus–pituitary area in 1.7%, CNS tumor distant from the hypothalamus–pituitary area in 0.68%, other tumors in 0.91%, congenital CNS malformations in 0.83%, and other diseases in 1.1% with their specific characteristics. The latest average age, height standard deviation score (SDS), insulin-like growth factor–1 SDS, and proportion of severe GHD at GH treatment initiation were 8.8 years, –2.76, –1.42, and 19.5%, respectively. The proportions of breech delivery and asphyxia gradually decreased, whereas that of caesarean section gradually increased during the registration period with the latest values of 2.2%, 4.9%, and 14.0%, respectively (all analyses: p < 0.0001). In contrast, the proportion of idiopathic GHD with breech delivery seemed to reach the lowest level among those with a birth year before 2000. This study identified the characteristics and changes of patients with GHD over 20 years.